Earnings tenure profiles: tests of agency and human capital theories using individual performance data - Xiao-yuan Dong; Derek C. Jones; Takao Kato (Institute for the Study of Labor (IZA), 2007)
By using a large new panel of individual data, including objective measures of worker performance, we provide some of the most rigorous evidence to date on several related dimensions of enduring debates surrounding upward-sloping earnings-tenure profiles. Most importantly we provide the first direct test of the relative validity of human capital and agency explanations in accounting for upward-sloping earnings-tenure profiles; our findings strongly support the agency view. Our second area of interest concerns employee ownership (many workers at our case are employee owners). Consistent with agency theory we find that earnings-tenure profiles for employee owners are not upward-sloping but horizontal. In addition we find that pay-performance sensitivities are substantially weaker for employee owners than for other workers. Finally we investigate the impact of residential policies in China. We find that again consistent with the agency view, earnings-tenure profiles are considerably steeper for urban workers than for migrant workers with far more limited alternative employment opportunities.
Keywords: 330; Earnings; tenure; seniority; performance; human capital; agency; employee ownership; Lohnstruktur; Betriebszugehörigkeit; Humankapital; Agency Theory; Arbeitsmobilität; Schätzung; China